Longitudinal Measurement Invariance of the PHQ-9 and GAD-7. (December 2022) - Ong, Clarissa W.; Pierce, Benjamin G.; Klein, Keith P.; Hudson, Chloe C.; Beard, Courtney; Björgvinsson, Thröstur
Intraindividual change over time is commonly used to estimate treatment effectiveness. However, patients may not respond similarly to a scale after treatment, rendering pre–post change an unreliable metric. The current objective was to investigate longitudinal measurement invariance of the Patient Health Questionnaire–9 and Generalized Anxiety Disorder Scale–7 among 4, 323 patients completing a partial hospital program. We used confirmatory factor analysis to determine (1) factor structure at pretreatment and posttreatment and (2) longitudinal invariance, accounting for dependent observations, using both classical and approximate measurement invariance approaches. Results indicated a two-factor solution for both scales. Longitudinal invariance was not established for either scale, thus, using raw score differences from the Patient Health Questionnaire–9 and Generalized Anxiety Disorder Scale–7 for measuring symptom change over time may be problematic. The most longitudinally consistent items captured somatic as opposed to affective/cognitive symptoms. We discuss the potential use of these measures for diagnostic screening and between-group comparisons and suggest alternative ways to monitor client progress over time. Limitations included a majority White sample and uniqueness of a partial hospital setting.